The main innovative methods of studying during the formation of professional competence of a psychologist - Boldyrev, Kyrylo (NTU "KhPI", 2018)
The article analyzes the main innovative teaching methods that are actively used in modern pedagogical practice. Their significance and place in the modern pedagogical hierarchy, the total amount of time allocated for their direct application in domestic pedagogical programs of psychologist training and the role of student and teacher in realization of innovative teaching methods were considered.

У статті проаналізовано основні інноваційні методи навчання, що активно використовуються у сучасній педагогічній практиці. Досліджено їх значення та місце у сучасній педагогічній ієрархії, визначено загальну кількість відведеного часу на їх пряме застосування у вітчизняних педагогічних програмах підготовки психолога та роль студента і викладача при реалізації інноваційних методів навчання.
Основні інноваційні методи навчання під час формування професійної компетентності психолога
Keywords: professional competence; innovative teaching methods; simulation methods; non-imitation methods; game methods; group methods; професійна компетентність; інноваційні методи навчання; імітаційні методи; неімітаційні методи; ігрові методи; групові методи